2021
DOI: 10.1017/ehs.2021.44
|View full text |Cite
|
Sign up to set email alerts
|

Women feel more attractive before ovulation: evidence from a large-scale online diary study

Abstract: How attractive we find ourselves decides who we target as potential partners and influences our reproductive fitness. Self-perceptions on women's fertile days could be particularly important. However, results on how self-perceived attractiveness changes across women's ovulatory cycles are inconsistent and research has seldomly assessed multiple attractiveness-related constructs simultaneously. Here, we give an overview of ovulatory cycle shifts in self-perceived attractiveness, sexual desirability, grooming, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 89 publications
(188 reference statements)
3
12
1
Order By: Relevance
“…The data was primarily collected to investigate psychological cycle shifts in women (Arslan et al, 2016). Arslan, Reitz, et al (2020) published a paper based on the data collection focusing on measurement arcana investigating the benefits of a planned missingness design in diary studies and Schleifenbaum et al (2021) studied fertile window effects on attractiveness on a within-subject level using hormonal contraceptive users as a quasi-control group who do not experience ovulation. A codebook for the full dataset including all measures is available at https://rubenarslan.github.io/gocd2 .…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…The data was primarily collected to investigate psychological cycle shifts in women (Arslan et al, 2016). Arslan, Reitz, et al (2020) published a paper based on the data collection focusing on measurement arcana investigating the benefits of a planned missingness design in diary studies and Schleifenbaum et al (2021) studied fertile window effects on attractiveness on a within-subject level using hormonal contraceptive users as a quasi-control group who do not experience ovulation. A codebook for the full dataset including all measures is available at https://rubenarslan.github.io/gocd2 .…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Importantly, although concealed ovulation has traditionally been equated with a lost oestrus in women, both are not necessarily equivalent 14 . While we found no evidence for cues to fertility in this sample, it has been shown that women exhibit robust increases in their sexual desire 19,20,24,44,81,82 and their self-perceived attractiveness and desirability 24,42,83 which might nudge women towards sexual behaviour when the possibility of conception maximises the benefit-cost ratio 84 and thus may constitute an oestrus-like phase. By applying high methodological rigour, this work advances our understanding of how ovulatory cycle changes are perceived by women's long-term partners and offers implications for the vibrant debate about the evolution of concealed ovulation and oestrus in women.…”
Section: Discussioncontrasting
confidence: 79%
“…Adhering to previously reported procedures 23,24,35,83 , we applied continuous estimates 91 to compute PBFW. Since ovulatory cycles naturally show considerable inter-and intraindividual variation 92 , we controlled for grave cycle irregularities by only considering cycles that were between 20 and 40 days long and did not count further back than 40 days from the next onset of menstrual bleeding.…”
Section: Estimating Women's Fertile Windowmentioning
confidence: 99%
“…It would be interesting for future researchers to consider whether these links vary over time, such as across menstrual phases. There is research showing how self-perceived attractiveness fluctuates across the phases of the menstrual cycle, with women in the periovulatory phase rating themselves as higher in mate value in comparison to lower fertile phases (Schleifenbaum et al, 2021 ). It is also important for future research to consider the potential limitations of self-reported mate value.…”
Section: Discussionmentioning
confidence: 99%